Malrotation with Distal Duodenal Necrosis in a Neonate - Vinit kumar Thakur; Digamber Chaubey; Vijayendra Kumar; Ramdhani Yadav; Deepak Kumar; Sandip Kumar Rahul (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Malrotation with midgut volvulus often results in gangrene of midgut with relative sparing of duodenum. An extremely unusual case of Malrotation with isolated necrosis of distal duodenum is described with brief review of literature. Isolated duodenal necrosis in association with malrotation is very rare; it increases the complexity of surgery and prolongs hospital stay.